Cités et Reterritorialisation: La France Ã l'Heure des Frandes Métropoles - Pastorel, Jean-Paul (Victoria University of Wellington Law Review, 2007)
The structure of local authority power in France, which is heir to a system of fractionalised communities and also to a tradition of downgrading of cities, is a matter of current interest today. This is largely because of the federalisation movement in Europe and the globalisation of economies within the European market. The federalisation movement has been beneficial - integrated inter-communal structures open the way to large metropolises. Metropolises in turn, are connected with more less vast regional areas thereby redrawing the contours of the new directions of development. In this paper on the evolution of the French territorial entities, the author makes clear the consistent way in which the French legislator has moved since the signing of the Treaty of Rome in 1957, to transform the way in which territorial institutions are organised. The re-organisation of the increasingly urban communities and regions will benefit from a "plan of re-territorialisation". The declared goal is to organise these areas by arranging a network of towns both small and medium sized around metropolises in order to create true competitive areas employment which have the capacity to stimulate economic activity. From being communities of citizens, these contiguous territorial entities, subject both to the rules of free competition and to Community norms, are progressively transformed into economic players. By confirming the role of territorial entities to take all the decisions which can best be exercised at the local level (the principle of subsidiarity), the French constitutional reform of 27 March 2003 paved the way for a degree of flexibility of territorial organisation which can lead to a type of decentralisation to suit each different situation, including by the state towards the territorial entities or between territorial entities. The break with traditional uniformity of the territorial groupings in France is part of the re-territorialisation of local government areas and thus is consonant with rapid metropolisation and market liberalisation.